Covid-19, tensiones entre China y Estados Unidos, y crisis del multilateralismo: repercusiones para AL - Bernal- Meza, Raúl (El Colegio de México A.C., 2021)
The article analyzes two ongoing international processes, the rivalry between China and the United States and the Covid-19 pandemic. The concurrence of the two has led to further deterioration of multilateralism. For Latin America, the confluence of these situations increase its vulnerability, exposing it to an international scenario of growing uncertainty, demonstrating its limited margin for maneuver. The text presents an analysis to help understand these global dynamics, based on a theoretical reflection about the conflict between powers and its consequences for foreign policy and the future of multilateralism. It also addresses the impact of Covid-19 and of tensions in the liberal international order, from the theoretical perspectives of cooperation: complex interdependence and liberal institutionalism, in order to understand how discord wins over collaboration. All these trends have a negative impact on a Latin America that rejects collective action, in its relations with both the United States and China.